Greenhouse gases modulate the strength of millennial-scale subtropical rainfall, consistent with future predictions - F. Guo; S. Clemens; Y. Liu; T. Wang; H. Fan; X. Liu; Y. Sun (Climate of the Past, 2022)
Millennial-scale East Asian monsoon variability is closely associated with natural hazards through long-term variability in flood and drought cycles. Therefore, exploring what drives the millennial-scale variability is of significant importance for future prediction of extreme climates. Here we present a new East Asian summer monsoon (EASM) rainfall reconstruction from the northwest Chinese Loess Plateau (CLP) spanning the past 650 kyr. The magnitude of millennial-scale variability (MMV) in EASM rainfall is linked to ice volume and greenhouse gas (GHG) at the 100 kyr eccentricity band and to GHG and summer insolation at the precession band. At the glacial–interglacial timescale, gradual changes in CO 2 during intermediate glaciations lead to increased variability in North Atlantic stratification and Atlantic meridional overturning circulation, propagating abrupt climate changes into East Asia via the westerlies. Within the 100 kyr cycle, precession variability further enhances the response, showing that stronger insolation and increased atmospheric GHG cause increases in the MMV of EASM rainfall. These findings indicate increased extreme precipitation events under future warming scenarios, consistent with model results.